Morin Protects Channel Catfish From Aeromonas hydrophila Infection by Blocking Aerolysin Activity - Dong, Jing; Liu, Yongtao; Xu, Ning; Yang, Qiuhong; Ai, Xiaohui (Frontiers in Microbiology, 2018)
Aeromonas hydrophila (A. hydrophila) is an opportunistic bacterial pathogen widely distributed in the environments, particular aquatic environment. The pathogen can cause a range of infections in both human and animals including fishes. However, the application of antibiotics in treatment of A. hydrophila infections leads to the emergence of resistant strains. Consequently, new approaches need to be developed in fighting this pathogen. Aerolysin, the chief virulence factor produced by pathogenic A. hydrophila strains has been employed as target identifying new drugs. In our present study, we found that morin, a flavonoid without anti-bacterial activity isolated from traditional Chinese medicine, could directly inhibit the hemolytic activity of aerolysin. To determine the binding sites and the action of mechanism of morin against AerA, several assays were performed. Ser36, Pro347, and Arg356 were identified as the main binding sites affecting the conformation of AerA and resulted in block of the heptameric formation. Moreover, morin could protect Vero cells from cell injury mediated by aerolysin. In vivo study showed that morin could provide a protection to channel catfish against A. hydrophila infection. These results demonstrated that morin could be developed as a promising candidate for the treatment of A. hydrophila infections by decreasing the pathogenesis of A. hydrophila.